2021
DOI: 10.3390/ma14154310
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Breathable Cellulose Based Polymeric Membranes with Enhanced Water Resistance for the Building Industry

Abstract: This study focuses on the development of advanced water-resistant bio-based membranes with enhanced vapour permeability for use within building envelopes. Building walls are vulnerable to moisture damage and mold growth due to water penetration, built-in moisture, and interstitial condensation. In this work, breathable composite membranes were prepared using micro-fibrillated cellulose fiber (CF) and polylactic acid (PLA). The chemical composition and physical structure of CF is responsible for its hydrophilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Moreover, the agglomeration of CMF in PLA and the formation of voids between the polymer matrix and fibers can create a preferential pathway for the transport of water vapor molecules in materials. Hussain and Blanchet (2021) previously demonstrated that the values of water vapor transmission increased by incorporating cellulose fibers into the PLA matrix.…”
Section: Bioresourcescommentioning
confidence: 98%
“…Moreover, the agglomeration of CMF in PLA and the formation of voids between the polymer matrix and fibers can create a preferential pathway for the transport of water vapor molecules in materials. Hussain and Blanchet (2021) previously demonstrated that the values of water vapor transmission increased by incorporating cellulose fibers into the PLA matrix.…”
Section: Bioresourcescommentioning
confidence: 98%
“…Its slight enhancement on the wet strength of the product could be due to the formed hydrogen bonding between CS and fibers. 28 , 29 …”
Section: Resultsmentioning
confidence: 99%
“…Its slight enhancement on the wet strength of the product could be due to the formed hydrogen bonding between CS and fibers. 28,29 Water Resistance of CS Wet-Added Pulp Molded Products. The contact angles of CS wet-added pulp molded products at various CS dosages are demonstrated in Figure 7.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is convinced by the transmission of water molecules in the microscopic pores of the fiber material which are filled with water because of capillary condensation 58 . For ingredients that display hysteresis in their sorption isotherm, it has been described previously that their WVTR is dependent on moisture content 59,60 . We detected that there is a small increase in water vapor transmission rate as the percentage of different ratios of treated fibers (Sub and SSF) from 10 to 20% increases.…”
Section: Water Vapor Transmission Rate (Wvtr) Ofmentioning
confidence: 99%